Hexokinases link DJ-1 to the PINK1/parkin pathway - David N. Hauser (Molecular Neurodegeneration, 2017)
Abstract Background Early onset Parkinson’s disease is caused by variants in PINK1, parkin, and DJ-1. PINK1 and parkin operate in pathways that preserve mitochondrial integrity, but the function of DJ-1 and how it relates to PINK1 and parkin is poorly understood. Methods A series of unbiased high-content screens were used to analyze changes at the protein, RNA, and metabolite level in rodent brains lacking DJ-1. Results were validated using targeted approaches, and cellular assays were performed to probe the mechanisms involved. Results We find that in both rat and mouse brains, DJ-1 knockout results in an age-dependent accumulation of hexokinase 1 in the cytosol, away from its usual location at the mitochondria, with subsequent activation of the polyol pathway of glucose metabolism in vivo. Both in the brain and in cultured cells, DJ-1 deficiency is associated with accumulation of the phosphatase PTEN that antagonizes the kinase AKT. In cells, addition of an inhibitor of AKT (MK2206) or addition of a peptide to dissociate association of hexokinases from mitochondria both inhibit the PINK1/parkin pathway, which works to maintain mitochondrial integrity. Conclusion Hexokinases are an important link between three major genetic causes of early onset Parkinson’s disease. Because aging is associated with deregulated nutrient sensing, these results help explain why DJ-1 is associated with age-dependent disease.